Media Pembelajaran Interaktif Pengenalan Alat Pembuatan Kain Batik Berbasis Android - Leni Fitriani; Dini Destiani Siti Fatimah; Larasyla Putriana Maharani (Jurnal Algoritma, 2022)
Interactive learning media can be an information technology that can convey new learning techniques using Android devices that aim to increase motivation and interest in learning as well as solutions or problem solvers. This interactive learning media is designed for all people, especially in the general environment as a learning media that is packaged as an android application so that learning is more effective and efficient. Not only providing knowledge and learning, but can give a pleasant impression to users. Learning media has great motor skills because it can transmit new experiences so that the information stored in it can be conveyed and remembered by all users, most of whom have a great desire to understand everything around them, even whatever they have just seen. This interactive learning media aims to provide a clear picture for students about the introduction of batik cloth making tools, increase motivation and interest and can eliminate boredom in learning. This interactive learning media for the introduction of batik cloth making tools uses the Luther-Sutopo version of the MDLC (Multimedia Development Lifecycle) method which has 6 steps, namely concept, design, material collecting, assembly, testing and distribution. This research creates an application that displays interactive learning media for the introduction of batik cloth making tools that can be accessed anywhere.